Noun group and its grammatical category........ - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Noun are part of speech that comprise words that are used to name people,places,animals, objects and ideas .Almost every sentence will definitely have a noun and they perform different roles in a sentence.Noun can act as the subject, an indirect object, a direct object a, subject complement.Nouns can also function as adjectives and verbs.